Die verbesserte Kontinenzleistung nach Pena-Operationen bei anorektalen Mißbildungen = Improved continence following the pena procedure for anorectal malformations - Benz, Gert; Kienle, Peter (Vielfalt und Einheit der Chirurgie Humanität und Wissenschaft, 1998)
Studies investigating the functional outcome after operative treatment of high and intermediate forms of anal and rectum atresia have shown better results for the Pena procedure than for other forms of pull-through procedures. Follow-up with three-dimensional vector volume manometry of patients operated on according to Pena and matched controls demonstrated a significant improvement in the radial asymmetry index over the years and must be interpreted as a maturation process of the continence organ on a critical level.